SDF-1 provides morphological and functional protection against renal ischaemia/reperfusion injury - Stokman, Geurt; Stroo, Ingrid; Claessen, Nike; Teske, Gwendoline J D; Florquin, Sandrine; Leemans, Jaklien C (Nephrology, dialysis, transplantation, 2010)
The chemokine stromal cell-derived factor-1 (SDF-1) is thought to be involved in mediating tissue repair by promoting migration of bone marrow stem or progenitor cells to the site of injury. Increased levels of renal SDF-1 are found after kidney injury. However, recently, we showed that SDF-1 does not play an important role in the migration of haematopoietic stem cells to the post-ischaemic kidney. The function of increased post-ischaemic renal SDF-1 expression in modulating renal ischaemia/reperfusion injury remains, therefore, unknown. We studied the role of SDF-1 in renal ischaemia/reperfusion injury by locally decreasing SDF-1 expression and subsequent SDF-1 signalling in the corticomedullary region of the kidney using antisense oligonucleotide treatment in mice. Renal SDF-1 protein increased significantly in the early phase of ischaemia/reperfusion injury. Antisense treatment resulted in a reduction of corticomedullary SDF-1 expression which was accompanied by severely increased tubular injury and decreased renal function. We did not observe any difference in mobilization or retention of CXCR4-positive haematopoietic stem or progenitor cells after induction of renal ischaemia. Rather, antisense-treated animals showed markedly increased apoptosis of the tubular epithelium accompanied by an increased renal inflammatory response. Conclusions. These data indicate a new role for SDF-1 in renal pathogenesis by mediating tubular epithelial protection against ischaemic injury and suggest that SDF-1 by itself is not crucial for the influx of haematopoietic stem or progenitor cells towards the ischaemic injured kidney.